(untitled) (Revista de História Regional, 2022)
This article was written with the precise purpose of bringing visibility to the artist and historian Sérgio Luiz de Castro Bonson’s work between 1974 and 2005. For that matter, regarding several pieces of Bonson’s extensive work, we simultaneously discuss art, city, politics and humor in Brazilian daily life in said time period. Bonson’s work has a strong link to the local culture set in Florianópolis (SC), not, however, disregarding a connection with the national and the transnational set. The text is divided in two parts. In the first part, we provide the reader with a display of Sérgio Bonson’s most local related work. In the second part, we discuss Bonson’s work concerning so called alternative or combative press. Combined, both parts pretentiously enclose an important majority of the resourceful work of Sérgio Bonson, an attentive artist and a historian of our sociocultural manifestations.